Gestão de avaliações externas em uma instituição jesuíta de educação básica: desafios e estratégias de replanejamento pedagógico - Bravo Neto, Estevam (Universidade do Vale do Rio dos Sinos, 2024)
This study aims to analyze how pedagogical replanning is perceived by the management and teaching staff of a Jesuit institution, part of the Jesuit Education Network (RJE). Based on the evidence obtained from external evaluations, the research seeks to identify the barriers that hinder the use of this data in the teaching-learning process. The research is grounded in behaviorist motivational theory, which provides a practical analysis of educators' behavioral responses to the stimuli provided by external evaluations. The methodology employed is qualitative, using document analysis and semi-structured interviews conducted with managers and teachers of the institution. The document analysis included the RJE’s Common Educational Project (PEC) and the school's Political Pedagogical Project (PPP), which provide insights into the institutional context and evaluative practices. The interview results identified the main challenges faced by teachers in implementing necessary changes based on the external evaluation data, such as limited time for replanning and a lack of alignment with management. The findings revealed that, despite positive perceptions regarding the usefulness of external evaluations, significant barriers exist in pedagogical replanning, especially related to work overload and the pressure to adhere to the curriculum schedule. As an intervention, the research proposes the creation of a working group responsible for mapping these difficulties and implementing a unified planning tool, integrating external evaluations into the pedagogical planning. The study concludes that, to improve the effectiveness of these evaluations, greater alignment between managers and teachers is essential, along with continuous support for replanning based on evidence generated by external evaluations.
Keywords: Replanejamento pedagógico; Avaliações externas; Gestão educacional; Teorias motivacionais; Pedagogical replanning; External evaluations; Educational management; Motivational theories; ACCNPQ::Ciências Humanas::Educação